تقويم أهداف منهج تعليم اللغة العربية في المرحلة الثانوية بجزر القمر (معاهد رابطة العالم الإسلامي أنموذجا) - حمد، حسين مزي (Ma'had al-Tarbiyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2010)
This study aims to identify the effectiveness of the curriculum objectives of teaching Arabic language in the secondary school in Comoros taking the institutions of Muslim league world in Comoros as model. Likewise its suitability to the philosophy of the national education, needs of the students, the Comorian environments and the extent of its achievement from the viewpoints of the teachers and the students. The research was conducted from the sample selection of 051 males and females students out of the total that consist of 482 students in three schools of the Great Comorian Island. This is out of the available five schools. The research also includes all the teachers of the schools who are 41 in number. The data was collected through the utilization of two close-ended questionnaires which each was given to the teachers and the students. The information was analyzed through the utilization of social science Statistical Package, which is known as (SPSS). The research was based on statistical frequency distribution, as well as percentage and the implementation of Alpha Cronbach for the confirmation of the reliability of the tools. The research concluded that the teachers are contented with the objectives of the curriculum of the teaching of Arabic language in the institution. The majority of the teachers also agree on its suitability of the level of the students. Most of the students agree on the linkage of the curriculum objectives with their ambitions in learning Arabic language, as they also agree on the competence of their teachers. Majority of teachers agree on the appropriateness of the curriculum objectives with the modern educational philosophy, 51: among them affirmed that, the curriculum objectives adjust with the Comorian environment, but most of them disagree on its suitability with the individual differences of the students, the needs of Comorian people and their hopes. Thus, base on the result of the research, the researcher offers some relevant suggestions, and recommendations for the enhancement of Arabic language in the institution.